(untitled) (Baghdad Science Journal, 2024)
Osteoarthritis (OA) is not an autoimmune but a chronic inflammatory disease affecting the joints of humans due to mechanical stress mostly in the knees and the hip. In OA a modification of the cartilage is encountered causing a pain in the joints upon movement. Coll2-1NO2 is a specific sequence of amino acids produced from the degradation of type II collagen, which is abundantly found in the cartilage, followed by a nitration in the tyrosine residue as a consequence of stress-inflammatory events. In this study, Coll2-1NO2 is used as a biomarker of OA to predict the inflammatory stress condition as well as the cartilage degradation in pre- and post-menopausal women. The results showed a significant increase of serum Coll2-1NO2 in pre- and post-menopausal women with OA compared to pre- and post-menopausal health women, at similar body mass index category (overweight). Pearson’s correlation analysis showed non-significant association between Coll2-1NO2 and other studied parameters. Moreover, ROC analysis showed a very excellent sensitivity of Coll2-1NO2 as a prognostic biomarker for OA disease in pre- and post-menopausal women